Use of robot‐specific resources and operating room times: the case of Telelap Alf‐X robotic hysterectomy. Issue 4 (8th January 2016) - Rossitto, Cristiano; Gueli Alletti, Salvatore; Romano, Federica; Fiore, Alessandra; Coretti, Silvia; Oradei, Marco; Ruggeri, Matteo; Cicchetti, Americo; Marchetti, Marco; Fanfani, Francesco; Scambia, Giovanni
Abstract: Introduction: The aim of this study was to identify, quantify and evaluate the use of robotic materials and operating theatre times in Telelap ALF‐X robotic hysterectomy. Materials and methods: Cost analysis was performed on 81 patients who underwent a Telelap ALF‐X robotic hysterectomy. Data were collected during a phase II study trial conducted at the University Hospital A. Gemelli, Catholic University, Rome. According to micro‐costing technique, surgical team costs, materials and operating theatre usage were recorded during each surgical intervention. Cost data were provided by the hospital's accounting office. Probabilistic sensitivity analysis was carried out in order to test the robustness of the results by assuming an Inv‐norm random variable. Results: The base case analysis showed a cost/patient of €3391.82. The new robotic device requires a low consumption of robotic materials. Sensitivity analysis showed that the most sensitive cost driver was use of the operating theatre. Conclusion: This study shows that Telelap ALF‐X robotic hysterectomy is feasible and safe and could offer specific advantages in terms of cost. Copyright © 2016 John Wiley & Sons, Ltd.